Low Chill Apple Cultivars for North Florida and North Central Florida - Peter C. Andersen (EDIS)
Provides guidance for homeowners in north and north central Florida to grow apple cultivars with low chilling requirement — how to locate them for best performance, suitable cultivars, acceptable rootstocks, planting, cultivation, fertilization, irrigation, training and pruning, harvesting and storage, and pest control.